ISOCHORIC HEAT CAPACITY OF 1% AQUEOUS SOLUTION OF MAGNESIUM CHLORIDE - V. I. Dvoryanchikov; D. K. Djavatov; G. A. Rabadanov; E. G. Iskenderov; D. P. Shikhakhmedova (Юг России: экология, развитие)
Aim. The aim is to conduct an experimental study of isochoric heat capacity of 1% aqueous solution of magnesium chloride along the phase boundary curve.Method. In order to determine the isochoric heat capacity at the phase boundary curve we used the adiabatic calorimeter of KH. I. Amirkhanov.Results. Results of the study of the isochoric heat capacity depending on the temperature are given in tables and figures; the findings are compared with those of other researchers. When evaluating a complex system, we ought not to evaluate its effectiveness on the basis of only one criterion, even a very important, in this case must take into account the requirements of the technical, economic, environmental and of other natures.Conclusions. When solving optimization problems of efficiency in geothermal energy it is necessary to take into account the fact of the temperature dependence of the heat and density. The temperature dependence of the density and heat capacity in the calculations significantly affect the value of the efficiency criterion to be taken into account, otherwise the calculation error can be up to 20%. The data obtained from the isochoric heat capacity of aqueous solutions of magnesium chloride is compared with the data for water and aqueous solutions of NaCl and NaOH, obtained previously, which may be represented as a model of geothermal and sea water.